Bronchial Lavage in the Treatment of Severe Bronchopulmonary Pathology in Adults. Approaches to Classification - E. U. Bonitenko; A. V. Shchegolev; S. A. Vasilev; N. A. Belyakova; A. I. Kuzmin; E. D. Sokolova (Неотложная медицинская помощь)
Introduction Currently, bronchial lavage (BL) is widely used in clinical practice for the treatment of severe bronchopulmonary lesion in adults. However, indications and contraindications for this procedure are not fully defined. In addition, it was not possible to find in the literature a classification of either BL in general or used for therapeutic purposes in particular, which significantly complicates the standardization of procedures for its use in various diseases.Aim of study To determine possible classification characteristics, as well as indications, contraindications for therapeutic BL in adults and possible complications that may arise, based on the analysis of literature data.Results Therapeutic BL can be carried out both as planned and for health reasons. Indications for planned BL are purulent bronchitis, pneumonia, purulentdestructive infiltration, as well as chronic lung diseases: bronchiectasis, interstitial lesions. In turn, the indication for emergency therapeutic BL is progressive acute or chronic respiratory failure, developing due to bronchial obstruction. Such conditions may include massive pulmonary hemorrhage, acute obstruction of the bronchi with mucus and pus, postoperative atelectasis and hypoventilation of the lungs, aspiration of gastric contents, severe bronchial asthma, purulent destruction of the lungs, acute respiratory distress syndrome, thermochemical lesions of the respiratory tract. Contraindications to therapeutic BL can be both absolute and relative. Absolute contraindications are intolerance to drugs used for local anesthesia; decompensated heart and (or) pulmonary failure; acute cerebrovascular accident; various types of arrhythmias; stenosis of the larynx and (or) trachea II–III degree; neuropsychiatric diseases; pain syndrome in the abdominal cavity; extremely serious condition of the patient, when clarification of the diagnosis can no longer affect treatment tactics. Relative contraindications include acute respiratory disease of the upper respiratory tract; coronary artery disease; severe diabetes mellitus; pregnancy (second half); chronic alcoholism; grade III enlargement of the thyroid gland. It should be noted that most of the absolute contraindications are conditional and are not taken into account when performing BL according to vital indications with appropriate medical and technical support. Classification of BL used for medicinal purposes can be carried out according to the following criteria: method of sanitation; access used; level of sanitation; sanitized area; volume and composition of the lavage solution. It is noteworthy that the methods of carrying out procedures for various conditions and diseases still remain unregulated. An exception is the final stage of the therapeutic BL procedure in the case of the use of surfactant preparations, which standardization is regulated by approved standard operating procedures. It should also be noted that bronchial lavage for therapeutic purposes is justified from a pathoanatomical and pathophysiological point of view, but is accompanied by serious, albeit temporary, changes in the lungs, which can be partially avoided by improving the lavage technique.Conclusion All of the above indicates that in order to solve existing problems, it is necessary to conduct systematic research in this direction with the involvement of all interested specialists.